Formula and preparation method of sterile grinding fluid for processing aluminum substrate of hard disk
By introducing sterile formulas and specific additives into the hard disk aluminum substrate abrasive solution, the existing abrasive solution has been solved, and higher processing quality and equipment cleanliness have been achieved.
Patent Information
- Application Number
- CN202411934224.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-15
AI Technical Summary
The abrasive liquid of existing hard disk aluminum substrates is inefficient and easy to introduce impurities. The growth of bacteria leads to clogging and surface quality problems, affecting processing accuracy and yield.
Provide a sterile abrasive solution formula for processing hard disk aluminum substrates, including sodium dodecyl sulfonate, fatty alcohol polyoxyethylene ether, potassium carbonate, antibacterial agent (such as nano zinc oxide) and water, combined with nano concave rod blending coupling agent and modified sodium alginate agent, and undergo high temperature sterilization.
It significantly improves the cooling effect and efficiency of the abrasive liquid, reduces the introduction of impurities and bacterial growth, ensures processing quality and equipment cleanliness, and reduces maintenance costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grinding liquid, and in particular to a formula of sterile grinding liquid for processing aluminum substrates of hard disks and a preparation method thereof. Background Art
[0002] There are many types of grinding fluids on the market with different functions. The current hard disk aluminum substrate grinding technology mostly relies on grinding fluids with cleaning, lubrication and cooling functions, but these grinding fluids often face the challenges of low efficiency and introduction of impurities, which significantly restricts the surface quality and yield rate of the substrate. What is more serious is that bacteria are easy to breed after the traditional grinding fluid is proportioned, resulting in the clogging of the grinding fluid and the bacteria remaining in the gaps of the grinding equipment, which seriously affects the processing accuracy and the surface quality of the substrate, becoming a major hidden danger in hard disk manufacturing. Based on this, the present invention provides a formula of sterile grinding fluid for hard disk aluminum substrate processing. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a formula of sterile grinding liquid for processing hard disk aluminum substrate and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a formula for sterile grinding liquid for processing aluminum substrates of hard disks, and the grinding liquid formula comprises the following raw materials in parts by weight: Sodium dodecyl sulfate 7 - 15 Fatty alcohol polyoxyethylene ether 10 - 20 Potassium carbonate 1 - 5 Antibacterial agent 1 Water 59 - 81.9.
[0005] Preferably, the antibacterial agent is nano zinc oxide.
[0006] Preferably, the grinding liquid further comprises 4-7 parts of nano-attapulgite blending coupling agent and 3-5 parts of modified sodium alginate agent.
[0007] Preferably, the preparation method of the nano-attapulgite-coupling agent is: S01: The nano-concave attapulgite is first heated to 220-230°C at a rate of 2-5°C / min, kept warm for 10-15min, then heated to 350-360°C at a rate of 1-3°C / min, kept warm for 5min, and finally air-cooled to room temperature to obtain a thermally improved nano-concave attapulgite; S02: Preparation of coupling blend: 3-5 parts of hydroxyapatite, 2-3 parts of silane coupling agent KH560, 4-7 parts of sodium lignin sulfonate solution and 2-4 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
[0008] The nano-attapulgite blending coupling agent adopts nano-attapulgite to be heat-improved first to optimize its active efficiency and interlamellar spacing, and then it is combined with coupling blending liquid for ball milling improvement. The raw materials in the coupling blending liquid are compounded with hydroxyapatite and other raw materials for coordinated synergy, which enhances the thermally improved nano-attapulgite, thereby significantly improving the antibacterial stability and antibacterial durability of the product.
[0009] Preferably, the mass fraction of the sodium lignin sulfonate solution is 4-7%.
[0010] Preferably, the preparation method of the modified sodium alginate agent is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of (3-5):5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 2-4 parts of dopamine hydrochloride solution and 2-3 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
[0011] The modified sodium alginate agent is treated with nano-silicon dioxide through a treatment liquid, and its activity performance and activity stability are improved. At the same time, it is stirred and fully treated in a dopamine hydrochloride solution and a sodium alginate solution, so as to better cooperate with the nano-attapulgite to adjust the coupling agent, and the performance of the product is further improved.
[0012] Preferably, the immersion ultrasonic treatment has an immersion power of 350-400 W and an immersion time of 1-2 h.
[0013] Preferably, the mass fraction of the dopamine hydrochloride solution is 3-6%; the mass fraction of the sodium alginate solution is 5-8%.
[0014] The present invention also provides a method for preparing a sterile grinding liquid formula for processing hard disk aluminum substrates, comprising the following steps: accurately weighing the above-mentioned components according to weight percentage, adding them into a stirring barrel in sequence, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
[0015] Preferably, the temperature for fully stirring and mixing at a constant temperature is 60-65° C., the stirring speed is 750-850 r / min, and the stirring is for 1 hour.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention currently has a wide variety of grinding fluids on the market with different functions, but the invention focuses on the innovation of sterile grinding fluid, the core of hard disk manufacturing, and is specially designed for hard disk aluminum substrate processing. This grinding fluid not only strengthens cooling, improves efficiency and surface gloss, but also integrates sterile formula and preparation process in a breakthrough way, aiming to significantly improve processing quality, greatly reduce grinding dirt, and ensure a sterile environment throughout the process, accurately meet the stringent requirements of high-precision and high-reliability hard disk manufacturing, and bring innovative solutions to the hard disk manufacturing field; the invention innovatively integrates antibacterial agents to develop sterile grinding coolant. The grinding fluid not only has a strong bactericidal ability and effectively curbs bacterial growth, but also ensures that there is no bacterial residue on the hard disk surface and grindstone gaps, significantly improving processing cleanliness. This move greatly reduces the frequency of grinding stone cleaning, reduces maintenance costs, and avoids surface defects caused by bacterial residues, bringing a double leap in higher quality and efficiency to hard disk manufacturing. DETAILED DESCRIPTION
[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The present embodiment provides a formula for sterile grinding liquid for processing aluminum substrates of hard disks, and the grinding liquid formula includes the following raw materials in parts by weight: Sodium dodecyl sulfate 7 - 15 Fatty alcohol polyoxyethylene ether 10 - 20 Potassium carbonate 1 - 5 Antibacterial agent 1 Water 59 - 81.9.
[0019] The antibacterial agent in this embodiment is nano zinc oxide.
[0020] The grinding liquid of this embodiment also includes 4-7 parts of nano-attapulgite blending coupling agent and 3-5 parts of modified sodium alginate agent.
[0021] The preparation method of the nano-attapulgite-coupling coupling agent of this embodiment is: S01: firstly heating to 220-230°C at a rate of 2-5°C / min, keeping the temperature for 10-15min, then heating to 350-360°C at a rate of 1-3°C / min, keeping the temperature for 5min, and finally air cooling to room temperature to obtain a thermally improved nano-attapulgite; S02: Preparation of coupling blend: 3-5 parts of hydroxyapatite, 2-3 parts of silane coupling agent KH560, 4-7 parts of sodium lignin sulfonate solution and 2-4 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
[0022] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 4-7%.
[0023] The preparation method of the modified sodium alginate agent of this embodiment is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of (3-5):5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 2-4 parts of dopamine hydrochloride solution and 2-3 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
[0024] The immersion power of the immersion ultrasonic treatment in this embodiment is 350-400W, and the immersion time is 1-2h.
[0025] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3-6%; the mass fraction of the sodium alginate solution is 5-8%.
[0026] The method for preparing a sterile grinding liquid formula for processing a hard disk aluminum substrate of the present embodiment comprises the following steps: accurately weighing the above components according to the weight percentage, adding them into a stirring barrel in sequence, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
[0027] In this embodiment, the temperature for fully stirring and mixing at a constant temperature is 60-65°C, the stirring speed is 750-850r / min, and the stirring is carried out for 1 hour.
[0028] Example 1. The present embodiment provides a formula for sterile grinding liquid for processing aluminum substrates of hard disks, and the grinding liquid formula includes the following raw materials in parts by weight: Sodium dodecyl sulfate 7 Fatty alcohol polyoxyethylene ether 10 Potassium carbonate 1 Antibacterial agent 1 Water 59.
[0029] The antibacterial agent in this embodiment is nano zinc oxide.
[0030] The grinding liquid of this embodiment also includes 4 parts of nano-attapulgite blending coupling agent and 3 parts of modified sodium alginate agent.
[0031] The preparation method of the nano-attapulgite-coupling coupling agent of this embodiment is: S01: firstly heating to 220°C at a rate of 2°C / min, keeping the temperature for 10min, then heating to 350°C at a rate of 1°C / min, keeping the temperature for 5min, and finally air cooling to room temperature to obtain a thermally improved nano-concave attapulgite; S02: Preparation of coupling blend: 3 parts of hydroxyapatite, 2 parts of silane coupling agent KH560, 4 parts of sodium lignin sulfonate solution and 2 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
[0032] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 4%.
[0033] The preparation method of the modified sodium alginate agent of this embodiment is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of 3:5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 2 parts of dopamine hydrochloride solution and 2 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
[0034] The immersion power of the immersion ultrasonic treatment in this embodiment is 350 W, and the immersion time is 1 hour.
[0035] The mass fraction of the dopamine hydrochloride solution in this embodiment is 3%; the mass fraction of the sodium alginate solution is 5%.
[0036] The method for preparing a sterile grinding liquid formula for processing a hard disk aluminum substrate of the present embodiment comprises the following steps: accurately weighing the above components according to the weight percentage, adding them into a stirring barrel in sequence, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
[0037] In this embodiment, the temperature for fully stirring and mixing at a constant temperature is 60° C., the stirring speed is 750 r / min, and the stirring is performed for 1 hour. Example
[0038] The present embodiment provides a formula for sterile grinding liquid for processing aluminum substrates of hard disks, and the grinding liquid formula includes the following raw materials in parts by weight: Sodium dodecyl sulfate 15 Fatty alcohol polyoxyethylene ether 20 Potassium carbonate 5 Antibacterial agent 1 Water 81.9.
[0039] The antibacterial agent in this embodiment is nano zinc oxide.
[0040] The grinding liquid of this embodiment also includes 7 parts of nano-attapulgite blending coupling agent and 5 parts of modified sodium alginate agent.
[0041] The preparation method of the nano-attapulgite-coupling coupling agent of this embodiment is: S01: firstly heating to 230°C at a rate of 5°C / min, keeping the temperature for 15min, then heating to 360°C at a rate of 3°C / min, keeping the temperature for 5min, and finally air cooling to room temperature to obtain a thermally improved nano-attapulgite; S02: Preparation of coupling blend: 5 parts of hydroxyapatite, 3 parts of silane coupling agent KH560, 7 parts of sodium lignin sulfonate solution and 4 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
[0042] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 7%.
[0043] The preparation method of the modified sodium alginate agent of this embodiment is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of 5:5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 4 parts of dopamine hydrochloride solution and 3 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
[0044] The immersion power of the immersion ultrasonic treatment in this embodiment is 400 W, and the immersion time is 2 h.
[0045] The mass fraction of the dopamine hydrochloride solution in this embodiment is 6%; the mass fraction of the sodium alginate solution is 8%.
[0046] The method for preparing a sterile grinding liquid formula for processing a hard disk aluminum substrate of the present embodiment comprises the following steps: accurately weighing the above components according to the weight percentage, adding them into a stirring barrel in sequence, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
[0047] In this embodiment, the temperature for fully stirring and mixing at a constant temperature is 65° C., the stirring speed is 850 r / min, and the stirring is performed for 1 hour.
[0048] Example 3. The present embodiment provides a formula for sterile grinding liquid for processing aluminum substrates of hard disks, and the grinding liquid formula includes the following raw materials in parts by weight: Sodium dodecyl sulfate 11.5 Fatty alcohol polyoxyethylene ether 15 Potassium carbonate 3 Antibacterial agent 1 Water 67.
[0049] The antibacterial agent in this embodiment is nano zinc oxide.
[0050] The grinding liquid of this embodiment also includes 5.5 parts of nano-attapulgite blending coupling agent and 4 parts of modified sodium alginate agent.
[0051] The preparation method of the nano-attapulgite-coupling coupling agent of this embodiment is: S01: firstly heating to 225°C at a rate of 3.5°C / min, keeping the temperature for 12.5min, then heating to 355°C at a rate of 2°C / min, keeping the temperature for 5min, and finally air cooling to room temperature to obtain a thermally improved nano-attapulgite; S02: Preparation of coupling blend: 4 parts of hydroxyapatite, 2.5 parts of silane coupling agent KH560, 5.5 parts of sodium lignin sulfonate solution and 3 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
[0052] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5.5%.
[0053] The preparation method of the modified sodium alginate agent of this embodiment is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of 4:5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 3 parts of dopamine hydrochloride solution and 2.5 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
[0054] The immersion power of the immersion ultrasonic treatment in this embodiment is 375 W, and the immersion time is 1.5 h.
[0055] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4.5%; the mass fraction of the sodium alginate solution is 6.5%.
[0056] The method for preparing a sterile grinding liquid formula for processing a hard disk aluminum substrate of the present embodiment comprises the following steps: accurately weighing the above components according to the weight percentage, adding them into a stirring barrel in sequence, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
[0057] In this embodiment, the temperature for fully stirring and mixing at a constant temperature is 62° C., the stirring speed is 800 r / min, and the stirring is performed for 1 hour.
[0058] Example 4. The present embodiment provides a formula for sterile grinding liquid for processing aluminum substrates of hard disks, and the grinding liquid formula includes the following raw materials in parts by weight: Sodium dodecyl sulfate8 Fatty alcohol polyoxyethylene ether 12 Potassium carbonate 3 Antibacterial agent 1 Water 65.
[0059] The antibacterial agent in this embodiment is nano zinc oxide.
[0060] The grinding liquid of this embodiment also includes 5.5 parts of nano-attapulgite blending coupling agent and 4 parts of modified sodium alginate agent.
[0061] The preparation method of the nano-attapulgite-coupling coupling agent of this embodiment is: S01: firstly heating to 222°C at a rate of 3°C / min, keeping the temperature for 12min, then heating to 352°C at a rate of 2°C / min, keeping the temperature for 5min, and finally air cooling to room temperature to obtain a thermally improved nano-attapulgite; S02: Preparation of coupling blend: 4 parts of hydroxyapatite, 2 parts of silane coupling agent KH560, 5 parts of sodium lignin sulfonate solution and 3 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
[0062] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%.
[0063] The preparation method of the modified sodium alginate agent of this embodiment is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of 4:5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 3 parts of dopamine hydrochloride solution and 3 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
[0064] The immersion power of the immersion ultrasonic treatment in this embodiment is 370 W, and the immersion time is 1.2 h.
[0065] The mass fraction of the dopamine hydrochloride solution in this embodiment is 4%; the mass fraction of the sodium alginate solution is 6%.
[0066] The method for preparing a sterile grinding liquid formula for processing a hard disk aluminum substrate of the present embodiment comprises the following steps: accurately weighing the above components according to the weight percentage, adding them into a stirring barrel in sequence, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
[0067] In this embodiment, the temperature for fully stirring and mixing at a constant temperature is 62° C., the stirring speed is 790 r / min, and the stirring is performed for 1 hour.
[0068] Comparative Example 1. The difference from Example 3 is that no nano-attapulgite and coupling agent are added.
[0069] Comparative Example 2. The difference from Example 3 is that no coupling blending liquid is added to the nano-attapulgite blending coupling agent.
[0070] Comparative Example 3. The difference from Example 3 is that hydroxyapatite and lanthanum oxide are not added to the coupling blending solution.
[0071] Comparative Example 4. The difference from Example 3 is that no modified sodium alginate agent is added.
[0072] Comparative Example 5. The difference from Example 3 is that no nano silicon dioxide agent is added to the modified sodium alginate agent.
[0073] The product performances of Examples 1-4 and Comparative Examples 1-5 of the present invention were tested under conventional conditions and placed in 2% hydrochloric acid mist for 12 hours to test the acid corrosion resistance of the products. The test results are as follows.
[0074]
[0075] It can be seen from Examples 1-4 and Comparative Examples 1-5 that the products of Examples 1-4 of the present invention have excellent antibacterial persistence, and the product has significant acid and rot resistance stability; The product does not contain any of the nano-attapulgite blending coupling agent and modified sodium alginate agent, and the performance of the product deteriorates significantly. The synergistic effect of the two agents can significantly improve the product performance. When no coupling blending liquid is added to the nano-attapulgite blending coupling agent, no hydroxyapatite and lanthanum oxide are added to the coupling blending liquid, and no nano-silica agent is added to the modified sodium alginate agent, the performance of the products tends to deteriorate. Only when the raw materials are obtained by the method of the present invention, the performance effect of the product is the most significant. Other methods are not as obvious as the effect of the present invention.
[0076] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0077] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A formula for sterile grinding fluid for processing aluminum substrates of hard disks, characterized in that: The grinding liquid formula includes the following raw materials in parts by weight: Sodium dodecyl sulfate 7 - 15 Fatty alcohol polyoxyethylene ether 10 - 20 Potassium carbonate 1 - 5 Antibacterial agent 1 Water 59 - 81.
9.
2. According to the formula of sterile grinding liquid for processing aluminum substrate of hard disk in claim 1, it is characterized in that: The antibacterial agent is nano zinc oxide.
3. According to the formula of sterile grinding liquid for processing aluminum substrate of hard disk according to claim 2, it is characterized in that: The grinding liquid also includes 4-7 parts of nano-attapulgite blending coupling agent and 3-5 parts of modified sodium alginate agent.
4. According to the formula of sterile grinding liquid for processing aluminum substrate of hard disk according to claim 3, it is characterized in that: The preparation method of the nano-attapulgite-coupling coupling agent is as follows: S01: The nano-concave attapulgite is first heated to 220-230°C at a rate of 2-5°C / min, kept warm for 10-15min, then heated to 350-360°C at a rate of 1-3°C / min, kept warm for 5min, and finally air-cooled to room temperature to obtain a thermally improved nano-concave attapulgite; S02: Preparation of coupling blend: 3-5 parts of hydroxyapatite, 2-3 parts of silane coupling agent KH560, 4-7 parts of sodium lignin sulfonate solution and 2-4 parts of lanthanum oxide are uniformly mixed to obtain a coupling blending solution; S03: The heat-modified nano-attapulgite and the coupling blending liquid are mixed in a weight ratio of 5:3 and subjected to ball milling treatment at a ball milling speed of 1500 r / min for 1 h. After the ball milling is completed, the mixture is filtered and dried to obtain the nano-attapulgite blending coupling agent.
5. According to the formula of sterile grinding liquid for processing aluminum substrate of hard disk according to claim 4, it is characterized in that: The mass fraction of the sodium lignin sulfonate solution is 4-7%.
6. According to the formula of sterile grinding liquid for processing aluminum substrate of hard disk as claimed in claim 3, it is characterized in that: The preparation method of the modified sodium alginate agent is: S11: mixing a 5% by mass sodium silicate solution, a 4% by mass chitosan solution and citric acid in a weight ratio of (3-5):5:1 to obtain a treatment solution; S12: immersing the nano-silica into a sufficient amount of treatment solution and subjecting it to ultrasonic treatment, after the immersion is completed, filtering and drying are performed to obtain the nano-silica agent; S13: 2-4 parts of dopamine hydrochloride solution and 2-3 parts of nano-silicon dioxide are added to the sodium alginate solution and stirred to be fully treated, and then filtered and dried to obtain a modified sodium alginate agent.
7. A sterile grinding liquid formula for processing aluminum substrates for hard disks according to claim 6, characterized in that: The immersion power of the immersion ultrasonic treatment is 350-400W, and the immersion time is 1-2h.
8. According to claim 6, a formula of sterile grinding liquid for processing aluminum substrates of hard disks, characterized in that: The mass fraction of the dopamine hydrochloride solution is 3-6%; the mass fraction of the sodium alginate solution is 5-8%.
9. A method for preparing a sterile grinding liquid formula for processing hard disk aluminum substrates according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: accurately weighing the above components according to the weight percentage, adding them into a stirring barrel in turn, and stirring and mixing them evenly at a constant temperature; then filtering to remove impurities and ensure the purity of the grinding liquid; and finally performing high-temperature sterilization at a sterilization temperature of 110°C.
10. The method for preparing a sterile grinding liquid formula for processing hard disk aluminum substrates according to claim 9, characterized in that: The temperature for fully stirring and mixing at a constant temperature is 60-65°C, the stirring speed is 750-850r / min, and the stirring is carried out for 1 hour.
Citation Information
Patent Citations
Cleaning liquid for grinding computer hard disk substrate
CN101260346A
Preparation method for surface polishing treatment liquid of aluminum sectional material
CN102352511A
Polishing composition for hard disk substrate, polishing method and manufacture method of substrate
CN102863943A
Oil-in-water emulsified diamond grinding solution and preparation method thereof
CN105349046A
Aluminium alloy alkaline grinding fluid
CN105710760A